The Potential of Bacillus sp.’s Isolate of Coffee Beans as Plant Pest Control Candidates - Ekowati, Christina Nugroho; Siallagan, Maria Denada; Sumardi, Sumardi; Rosa, Emantis (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2022)
Long-term use of chemical pesticides in high doses might result in chemical residues. Therefore, eco-friendly plant pest control should be getting more attention. To do so, one might consider the utilization of microorganisms that have the enzymatic ability to destroy the pest's body structure. This study aimed to explore the isolates of Bacillus sp. from coffee beans as a plant pest control candidate. Bacillus could be considered due to its ability to produce protein crystals and extracellular enzymes. Three isolates are obtained from isolation from coffee beans: Bacillus sp. 1; Bacillus sp. 2; and Bacillus sp. 3. These isolates have the enzymatic character of protease, chitinase, and lipase. The results of the bioassay test on larvae of Plutella xylostella (Lepidoptera order) showed that these isolates were able to cause larvae death within 48 hours.